Copper slurry for high-strength low-temperature co-fired ceramic and preparation method of copper slurry
By using a combination of 70-85 wt% fine copper powder, 0.1-5% inorganic glass powder and organic carrier in the copper slurry, the problems of easy oxidation and poor dispersion after sintering of the copper slurry are solved, and the effects of high fine line resolution, good printing performance and low square resistance are achieved.
Patent Information
- Application Number
- CN202510134737.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-05-23
AI Technical Summary
The existing copper slurry is easily oxidized after sintering, resulting in increased square resistance of the film layer and poor conductivity. At the same time, the fine copper powder is prone to agglomeration and poor dispersion, resulting in low thin line resolution and poor printing performance.
Copper slurry is prepared by rolling 70-85 wt% fine copper powder, 0.1-5% inorganic glass powder and a residual amount of organic carrier. The inorganic glass powder consists of CaO, B2O3, SiO2, MgO, AlF3 and ZrO2, and the fine copper powder consists of the first copper powder and the second copper powder. The organic carrier is combined with the organic carrier to improve printing performance and fine line resolution.
The thin line resolution and printing performance of the copper slurry are improved, the square resistance after sintering is reduced and the conductivity is improved. At the same time, the bonding force between the inorganic glass powder and the ceramic substrate is enhanced, and the substrate warping is avoided.
Smart Images

Figure CN120032939A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a copper slurry for high-strength low-temperature co-fired ceramics and a preparation method thereof. Background Art
[0002] With the rapid development of industries such as aerospace, new energy vehicles, 5G communications, smart terminals and the Internet of Things, electronic components are gradually moving towards miniaturization, lightness and multifunctionality. The wiring density and functionality of electronic components are constantly improving, which puts higher requirements on the packaging technology that carries electronic components. As an important ceramic packaging technology in electronic packaging, low temperature co-fired ceramic (LTCC) technology has the advantages of adjustable dielectric properties, low dielectric loss, excellent high-frequency performance, small conductor square resistance and high wiring density. It is an important means to achieve system miniaturization, integration, multifunctionality and high reliability.
[0003] At present, the electronic paste commonly used in LTCC metallization electrodes is precious metal paste mainly composed of Au, Ag, Pt, Pd, etc., which results in high processing costs for ceramic substrates and seriously affects the promotion and application of LTCC packaging products. The price of metal copper is relatively low, and it has the advantages of high electrical conductivity and high thermal conductivity. It can replace precious metals such as Au, Ag, Pt, Pd as the paste system for LTCC metallization electrodes. Due to the unstable and easy oxidation characteristics of metal copper, the square resistance of the metallized film increases and the conductivity deteriorates after the copper paste is sintered; in addition, the fine copper powder is easy to agglomerate and has poor dispersion, resulting in low fine line resolution and poor printing performance of the copper paste. Therefore, it is urgent to develop a new type of copper paste to solve the problems of easy oxidation of copper paste after sintering, increased film resistance, low fine line resolution and poor printing performance of copper paste. Summary of the invention
[0004] In view of this, it is necessary for the present invention to provide a copper slurry for high-strength, low-temperature co-fired ceramics, which can not only solve the problem that the copper slurry is easily oxidized after sintering and the film layer has a large square resistance, but also overcome the difficulty that the fine copper powder is easy to agglomerate and has poor dispersibility, thereby improving the fine line resolution of the copper slurry and improving the printing performance of the copper slurry.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a copper slurry for high-strength low-temperature co-fired ceramics, which is rolled from 70-85wt% fine copper powder, 0.1-5% inorganic glass powder and the remainder organic carrier;
[0007] Wherein, the inorganic glass powder is composed of CaO, B 2 O 3 、SiO2 、MgO、AlF 3 and ZrO 2 The components are as follows: CaO is 20-40%, B 2 O 3 15~35%, SiO 2 25-40%, MgO 3-10%, AlF 3 0.1~5%, ZrO 2 It is 0.1~5%.
[0008] In a further embodiment, the fine copper powder consists of a first copper powder and a second copper powder.
[0009] Preferably, the D50 of the first copper powder is 0.4-0.9 μm, and the tap density is 3.8-4.5 g / cm 3 The D50 of the second copper powder is 1.0-2.5 μm, and the tap density is 4.5-5.5 g / cm 3 .
[0010] In a further embodiment, the organic carrier comprises, by mass percentage, 5-25% of thickener, 60-90% of solvent, and 3-20% of organic additive.
[0011] In a further embodiment, the thickener includes ethyl cellulose and acrylic resin, and the proportions of each component are respectively: 40-80% of ethyl cellulose and 20-60% of acrylic resin by mass.
[0012] In a further embodiment, the solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and terpineol.
[0013] In a further embodiment, the organic additive is selected from at least one of fish oil, span and lecithin.
[0014] The present invention further discloses a method for preparing the copper slurry as described above, comprising the following steps:
[0015] The copper powder, inorganic glass powder and organic carrier are fully mixed according to the ratio to obtain a slurry;
[0016] The slurry is rolled for multiple times until the slurry fineness reaches the requirement of screen printing, thereby obtaining copper slurry.
[0017] In a further embodiment, the preparation process of the inorganic glass powder is: after the components in the inorganic glass powder are evenly mixed, the mixture is subjected to high-temperature melting, water quenching, ball milling, drying, and sifting through a 300-mesh sieve for later use; and / or, the preparation process of the organic carrier is: after the components in the organic carrier are evenly mixed, the mixture is heated and stirred at 50-100° C. until a uniform paste is formed, and then cooled to room temperature for later use.
[0018] The present invention has the following beneficial effects:
[0019] 1) In the present invention, a first copper powder and a second copper powder are combined. The copper paste prepared by combining the two copper powders with an organic carrier has good printing performance, no burrs or jagged edges, and a fine line resolution (line width / line spacing) of up to 75±10μm / 75±10μm; at the same time, the combination of the two copper powders can improve the conductivity of the copper film layer, so that the square resistance of the copper paste is smaller.
[0020] 2) The present invention provides a specific inorganic glass powder, the composition type of the inorganic glass powder is similar to the type of high-strength, low-temperature co-fired ceramic substrate material, so that the prepared copper slurry and the high-strength, low-temperature co-fired ceramic substrate have good consistency in sintering shrinkage, and will not cause warping of the substrate; at the same time, during the sintering process, the inorganic glass powder is combined with the ceramic substrate, the material composition of the two is similar, and the inorganic glass powder is integrated into the ceramic matrix, which improves the adhesion between the ceramic substrate and the copper film layer, and the obtained copper slurry has better conductivity and lower square resistance after sintering. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a printing effect diagram of the copper paste prepared in Example 1. DETAILED DESCRIPTION
[0022] In order to describe the embodiments of the present invention in detail below, the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0024] The first aspect of the present invention discloses a copper slurry for high-strength low-temperature co-fired ceramics, which is rolled from 70-85wt% fine copper powder, 0.1-5% inorganic glass powder and the balance organic carrier;
[0025] Wherein, the inorganic glass powder is composed of CaO, B 2 O 3 、SiO 2 、MgO、AlF 3 and ZrO 2 composition.
[0026] Preferably, the components of the inorganic glass powder are as follows: CaO is 20-40%, B 2 O 3 15~35%, SiO 225-40%, MgO 3-10%, AlF 3 0.1~5%, ZrO 2 It is 0.1~5%.
[0027] In a further embodiment, the fine copper powder consists of a first copper powder and a second copper powder.
[0028] Preferably, the D50 of the first copper powder is 0.4-0.9 μm, and the tap density is 3.8-4.5 g / cm 3 The D50 of the second copper powder is 1.0-2.5 μm and the tap density is 4.5-5.5 g / cm 3 . Generally speaking, the D50 value of copper powder is related to the size of the copper powder particle size. The smaller the powder particle size, the easier it is for the powder to agglomerate and difficult to disperse, which reduces the printability of the copper slurry, and burrs and jagged edges appear. In addition, because the powder particle size is too small, the sintering shrinkage rate of the slurry increases, the sintering shrinkage rate of the slurry and the substrate does not match, and the substrate warps. If the powder particle size is too large, the fineness of the copper slurry increases, the printing performance of the slurry deteriorates, and the resolution of fine lines decreases. When the tap density of the copper powder is large, the gaps between the powder particles are small, the filling degree of the copper powder is high, the volume change required for the recrystallization of the copper powder particles during the sintering process is small, the connection between the copper powders is tighter, and the conductivity of the prepared copper slurry is better. In addition, small-particle copper powder is used in combination with large-particle copper powder, in which the small-particle copper powder is filled into the gaps between the large-particle copper powders, and the copper film layer is denser and more conductive after sintering.
[0029] In a further embodiment, the organic carrier comprises, by mass percentage, 5-25% of thickener, 60-90% of solvent, and 3-20% of organic additive.
[0030] In a further embodiment, the thickener comprises ethyl cellulose and acrylic resin, and the proportions of the components are respectively 40-80% of ethyl cellulose and 20-60% of acrylic resin by mass percentage.
[0031] In a further embodiment, the solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and terpineol; and the organic additive is selected from at least one of fish oil, span and lecithin. It is understood that the selection of solvents and organic additives is not limited to the above examples, and any conventionally used in the art can be used.
[0032] The second aspect of the present invention provides a method for preparing the copper slurry according to the first aspect of the present invention, comprising the following steps:
[0033] The fine copper powder, inorganic glass powder and organic carrier are fully and uniformly mixed according to the ratio to obtain a slurry; the mixing method is not particularly limited, such as using a high-speed stirring method. In some typical embodiments of the present invention, stirring at a speed of 600 to 2000 rpm for 2 to 20 minutes is sufficient.
[0034] The slurry is rolled for multiple times until the slurry fineness meets the requirements of screen printing to obtain copper slurry. It is understood that the slurry can be rolled using a three-roller mill, and the specific number of times is not particularly limited, as long as the slurry fineness meets the requirements.
[0035] Among them, the preparation of inorganic glass powder and organic carrier can be carried out according to the process well known to those skilled in the art. In some typical embodiments of the present invention, the preparation process of the inorganic glass powder is: after the components in the inorganic glass powder are evenly mixed, high-temperature melting, water quenching, ball milling, drying, and passing through a 300-mesh sieve for use; and / or, the preparation process of the organic carrier is: after the components in the organic carrier are evenly mixed, heating and stirring at 50-100°C until a uniform paste is formed, and then cooling to room temperature for use.
[0036] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.
[0037] Example 1
[0038] A copper paste for high-strength low-temperature co-fired ceramics, the copper paste comprises the following components by mass percentage: 70% fine copper powder, 5% inorganic glass powder, and 25% organic carrier. Among them, the fine copper powder, by mass percentage of the total raw materials, is 35% of the first copper powder, with a particle size of 0.8 μm and a tap density of 4.0 g / cm 3 The second copper powder is 35%, the particle size is 2.0 μm, and the tap density is 4.8 g / cm 3 ; The components of the inorganic glass powder are as follows by mass percentage: CaO is 30%, B 2 O 3 29%, SiO 2 30%, MgO 5%, AlF 3 is 3%, ZrO 2 The organic carrier is calculated by mass percentage of the total raw materials, and the thickener is 3.2% of ethyl cellulose, 1% of acrylic resin, the organic solvent is 9.4% of pinene alcohol, 9.4% of diethylene glycol butyl ether, and the organic additive is 1% of fish oil and 1% of lecithin.
[0039] The preparation method of the copper slurry comprises the following specific steps:
[0040] Preparation of inorganic glass powder: weigh the components of the inorganic glass powder in proportion, stir and mix, and then perform high temperature melting, water quenching, ball milling, drying, and passing through a 300-mesh sieve for later use;
[0041] Preparation of organic carrier: weigh thickener, organic solvent and organic additive according to proportion, add into double-layer glass reactor, first add organic solvent and organic additive and stir evenly, set heating temperature to 70°C, stirring speed to 240r / min, then slowly add thickener while stirring until a uniform paste is formed, cool to room temperature for use;
[0042] Preparation of copper slurry: weigh organic carrier, inorganic glass powder and fine copper powder into a stirring tank according to the ratio, put the stirring tank into a homogenizer, and stir at high speed to make them evenly mixed, wherein the stirring speed is 1000r / min, and the stirring time is 10 minutes; the mixed slurry is rolled into a paste slurry with a three-roll machine until the slurry fineness meets the requirements of screen printing to obtain the required copper slurry.
[0043] Figure 1 This is a printing effect diagram of the copper paste prepared in Example 1, and it can be seen that the copper paste has excellent printing performance.
[0044] Example 2
[0045] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0046] Example 3
[0047] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0048] Comparative Example 1
[0049] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0050] Comparative Example 2
[0051] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0052] Comparative Example 3
[0053] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0054] Comparative Example 4
[0055] The proportion of each component of the inorganic glass powder and the preparation method of the copper slurry in this embodiment are the same as those in Example 1, except that the types and proportions of the copper slurry components are different, as shown in Table 1.
[0056] Comparative Example 5
[0057] The composition, proportion and preparation method of the copper paste in this comparative example are the same as those in Example 1, except that the components of the inorganic glass powder are respectively as follows: CaO is 33%, B 2 O 3 29%, SiO 2 30%, MgO 5%, ZrO 2 It is 3%, as shown in Table 1 for details.
[0058] Comparative Example 6
[0059] The proportion of each component of inorganic glass powder and the type, proportion and preparation method of copper slurry in this comparative example are the same as those in Example 1, except that the particle size of the first copper powder is 0.8 μm and the tap density is 2.3 g / cm 3 The particle size of the second copper powder is 2.0 μm and the tap density is 3.2 g / cm 3 , as shown in Table 1.
[0060] Table 1 Composition and ratio of copper slurry
[0061]
[0062] The products prepared in the above Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to performance tests, and the results are shown in Table 2:
[0063] Table 2 Performance test of copper slurry
[0064]
[0065] It can be seen from the results in Table 2 that, by comparing Examples 1 to 3 with Comparative Examples 1 to 2, the fine copper powder is used in combination with the first copper powder and the second copper powder, which can improve the printing performance and fine line resolution of the copper paste. The printing performance of the paste of Comparative Examples 1 to 2 is poor, which may cause the bonding between the paste and the ceramic to decrease; at the same time, the combination of the two copper powders can improve the conductivity of the copper film layer, so that the square resistance of the copper paste is smaller. By comparing Examples 1 to 3 with Comparative Examples 3 to 4, the addition of inorganic glass powder bonding phase to the copper paste increases the bonding between the copper paste and the high-strength, low-temperature co-fired ceramics and improves the adhesion of the copper film layer; when the content of inorganic glass powder in the paste is relatively high (6wt%), the square resistance increases and the adhesion of the film layer decreases slightly. By comparing Examples 1 to 3 with Comparative Example 5, the inorganic glass powder in the copper paste contains AlF 3 , so that the softening point of the inorganic glass powder is reduced, the glass powder can fully wet the copper powder during the sintering of the copper slurry, promote the sintering of the slurry, reduce the square resistance of the copper slurry, and improve the adhesion of the copper film layer. By comparing Examples 1 to 3 with Comparative Example 6, the D50 of the first copper powder in the copper slurry is 0.4 to 0.9 μm, and the tap density is 3.8 to 4.5 g / cm 3 The D50 of the second copper powder is 1.0-2.5 μm, and the tap density is 4.5-5.5 g / cm 3 After sintering, the copper slurry has better conductivity, lower square resistance and stronger adhesion. This is because the greater the tap density of the copper powder, the smaller the sintering shrinkage, and it is easier to form a dense conductive network, thereby improving the conductivity and adhesion of the copper film layer.
[0066] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0067] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A copper slurry for high-strength low-temperature co-fired ceramics, characterized in that: It is rolled from 70-85wt% fine copper powder, 0.1-5% inorganic glass powder and the balance organic carrier; Wherein, the inorganic glass powder is composed of CaO, B2O3, SiO2, MgO, AlF3 and ZrO2.
2. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 1, characterized in that: The components of the inorganic glass powder are respectively as follows by mass percentage: CaO is 20-40%, B2O3 is 15-35%, SiO2 is 25-40%, MgO is 3-10%, AlF3 is 0.1-5%, and ZrO2 is 0.1-5%.
3. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 1, characterized in that: The fine copper powder is composed of a first copper powder and a second copper powder; the D50 of the first copper powder is 0.4-0.9 μm, and the tap density is 3.8-4.5 g / cm 3 The D50 of the second copper powder is 1.0-2.5 μm and the tap density is 4.5-5.5 g / cm 3 .
4. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 1, characterized in that: The organic carrier comprises the following components by mass percentage: 5-25% of a thickener, 60-90% of a solvent and 3-20% of an organic additive.
5. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 4, characterized in that: The thickener comprises ethyl cellulose and acrylic resin; in terms of mass percentage, the proportions of the components are: 40-80% of ethyl cellulose and 20-60% of acrylic resin.
6. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 4, characterized in that: The solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and terpineol.
7. The copper slurry for high-strength low-temperature co-fired ceramics according to claim 4, characterized in that: The organic additive is selected from at least one of fish oil, span and lecithin.
8. The method for preparing the copper slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: The fine copper powder, inorganic glass powder and organic carrier are fully and uniformly mixed according to the proportion to obtain a slurry; The slurry is rolled for multiple times until the slurry fineness reaches the requirement of screen printing, thereby obtaining copper slurry.
9. The preparation method according to claim 8, characterized in that: The preparation process of the inorganic glass powder is as follows: after the components of the inorganic glass powder are uniformly mixed, the mixture is melted, water quenched, ball milled, dried, and sieved for later use; And / or, the preparation process of the organic carrier is: after uniformly mixing the components in the organic carrier, heating and stirring at 50-100° C. until a uniform paste is formed, cooling to room temperature for use.
Citation Information
Cited By
Preparation method of cold-peelable high-performance conductive copper film
CN120878351A